2008
DOI: 10.1038/jp.2008.170
|View full text |Cite
|
Sign up to set email alerts
|

Meconium-induced release of nitric oxide in rabbit alveolar cells

Abstract: Previous studies have shown meconium-induced lung injury occurs throughout release of inflammatory cytokines. The exact mechanism of cytokine-induced apoptosis is not known. In this study we hypothesized that meconium-induced apoptosis in the lungs is mediated through the production of inducible nitric oxide (NO). We studied two groups of newborn rabbit pups: one group was instilled with meconium and other with normal saline. We measured precursors of NO in lung lavage from both groups of rabbits and NO levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Therefore, the association between elevated nitrite levels and reduced lung cell viability following meconium stimulation suggests that NO may play an important role in the pathogenesis of meconium-associated lung injury. The involvement of NO in meconium-associated lung injury has previously been studied [ 41 , 95 , 96 , 97 , 98 , 99 ]. Although the idea that elevated levels of NO might contribute to tissue damage is not new, our results showed HEL299 cells generated higher nitrite levels than A549 cells ( Figure 3 ); therefore, previous experiments using A549 cells may not accurately represent the extent of lung injuries caused by meconium exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the association between elevated nitrite levels and reduced lung cell viability following meconium stimulation suggests that NO may play an important role in the pathogenesis of meconium-associated lung injury. The involvement of NO in meconium-associated lung injury has previously been studied [ 41 , 95 , 96 , 97 , 98 , 99 ]. Although the idea that elevated levels of NO might contribute to tissue damage is not new, our results showed HEL299 cells generated higher nitrite levels than A549 cells ( Figure 3 ); therefore, previous experiments using A549 cells may not accurately represent the extent of lung injuries caused by meconium exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies of animals and cell lines examining the effects of meconium exposure have indicated the involvement of inflammatory mediators, such as NO and COX [ 41 , 95 , 96 , 97 , 98 ]. NO is required for vasodilation in PPHN and may cause other pathological changes in the body associated with the activation of inflammatory cells and cytokines, especially during lung injury [ 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the association between elevated nitrite levels and reduced lung cell viability following meconium stimulation suggests that NO may play an important role in the pathogenesis of meconium-associated lung injury. The involvement of NO in meconium-associated lung injury has previously been studied [41,[95][96][97][98][99]. Although the idea that elevated levels of NO might contribute to tissue damage is not new, our results showed HEL299 cells generated higher nitrite levels than A549 cells (Figure 3); therefore, previous experiments using A549 cells may not accurately represent the extent of lung injuries caused by meconium exposure.…”
Section: Discussionmentioning
confidence: 67%
“…Various studies of animals and cell lines examining the effects of meconium exposure have indicated the involvement of inflammatory mediators, such as NO and COX [41,[95][96][97][98]. NO is required for vasodilation in PPHN and may cause other pathological changes in the body associated with the activation of inflammatory cells and cytokines, especially during lung injury [100,101].…”
Section: Discussionmentioning
confidence: 99%
“…Meconium is a potent activator of a complement which is likely associated with systemic inflammatory response and oxidative burst ). Furthermore, exposure to meconium enhances production of NO and its derivatives (Fontanilla et al 2008), and triggers a significant oxidative stress leading to peroxidation of lipids (demonstrated by TBARS) and proteins (expressed by 3-nitrotyrosine, dityrosine, lysinelipid peroxidation products etc.) in the lung (Mokra et al 2007) and increases the oxidation markers also in the plasma (Kopincova et al 2014.…”
Section: Model Of Meconium Aspiration Syndrome Induced By Intratrachementioning
confidence: 99%